International employment contract - Rodríguez Rodrigo, Juliana (LABOS Revista de Derecho del Trabajo y Protección Social, 2024)
In this article we will explain when an employment contract is international and we will see, in this case, which European courts will be jurisdiction to hear the claims that arise in relation to it and the law that they will apply to resolve them. We will approach the study, therefore, from the perspective of Private International Law and we will analyze the main European rules regulating international jurisdiction and the applicable law in this matter of individual employment contract.
Keywords: employment contract; jurisdiction; Brussels I bis Regulation; applicable law; Rome I Regulation